Policies of Memory on Human Rights Violations in Recent History: A Bibliographic Review from 2008 through 2018 - Arboleda-Ariza, Juan Carlos; Piper-Shafir, Isabel; Vélez-Maya, Margarita María (Revista Mexicana de Ciencias Políticas y Sociales, 2020)
The study of policies of memory regarding human rights violations in military dictatorships, armed conflicts and civil wars in recent world history has had an important boom in recent decades, constituting grounds for symbolic disputes. The objective of this text was to conduct a bibliographic review of the work that has been developed around official and unofficial memory policies in the last ten years. The search yielded a result of 128 publications in databases such as SCOPUS, EBSCO, WOS, Science Direct, Scielo and Dialnet. The analysis of these publications allowed for the identification of conceptualizations, characterizations and theoretical approaches around memory policies. The presence of a memorial model centered on victims is discussed, their stories being the most prominent in memory policies and their pain being the main asset for their construction.